PENGARUH KETERAMPILAN, LINGKUNGAN KERJA, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJAPEGAWAI PADA DINAS KOMUNIKASI DAN INFORMATIKA (KOMINFO) KABUPATEN LABUHANBATU - Sulfia, Nur Indah (Jurnal Manajemen Akuntansi (JUMSI), 2021)
This study aims to determine the effect of skills, work environment, motivation and work discipline on employee performance on employee performance at the Office of Communication and Information Technology (KOMINFO) Labuhanbatu Regency. This type of research is associative research. Data collection in this study was conducted through a survey approach with quantitative descriptive research type by distributing questionnaires to 48 respondents, while the population used in this study were Employees at the Employee Performance at the Office of Communication and Informatics (KOMINFO) Labuhanbatu Regency. Data collection techniques were carried out by interviews, questionnaires. and documentation study. The data analysis tool used in this study was SSPS (Statistical Product Software Solution). The data analysis technique in this research is descriptive analysis, multiple linear regression analysis, hypothesis testing using partial significance test (t test), simultaneous significant testing (F test), and determination coefficient testing (R2). The results of this study indicate partially (t test) it is known that skills have a significant effect on Employee Performance at the Office of Communication and Information Technology (KOMINFO) Labuhanbatu Regency. Work Environment has a significant effect on Employee Performance on Employee Performance at the Office of Communication and Information Technology (KOMINFO) Labuhanbatu Regency. Motivation has a significant effect on Employee Performance at the Office of Communication and Information Technology (KOMINFO) Labuhanbatu Regency Then Work Discipline has a significant effect on Employee Performance on Employee Performance at the Office of Communication and Information Work Environment, Motivation and Work Discipline have a significant effect on Employee Performance at the Labuhanbatu Regency Communication and Information Service (KOMINFO) Through testing the coefficient of determination (R Square) 69.9% means that Skills, Work Environment, Motivation, and Work Discipline have a significant effect on Employee Performance3, The remaining 83% 3.25% is influenced by other variables that were not examined in this study.